2004
DOI: 10.1097/01.ju.0000132135.18093.d6
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Biopsy Gleason Grade: Implications for Counseling Patients With Biopsy Gleason Score 6 Prostate Cancer

Abstract: Gleason grade on needle biopsy is an inexact predictor of the final grade following radical prostatectomy. Patients with biopsy Gleason score 6 who are under graded are at significantly higher risk for adverse pathological features and biochemical recurrence than patients who remain with Gleason score 6 or less on final pathology findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 20 publications
6
44
0
1
Order By: Relevance
“…Ishizaki et al studied 144 consecutive patients with localized or locally advanced PCa and observed that the pathological stage tended to be skewed to a lower stage (65.3% pT2 and 33.9% pT3 (25). The concordance of GS between the biopsy and RRP specimens in this study (55%) was similar to that found in two previous studies (22,26), in which the authors found concordance rates of 56% and 62%, respectively.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Ishizaki et al studied 144 consecutive patients with localized or locally advanced PCa and observed that the pathological stage tended to be skewed to a lower stage (65.3% pT2 and 33.9% pT3 (25). The concordance of GS between the biopsy and RRP specimens in this study (55%) was similar to that found in two previous studies (22,26), in which the authors found concordance rates of 56% and 62%, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…This finding could also be explained by the different variables associated with the biopsy, including the gauge of the biopsy needle, the amounts of normal tissue and cancer in the biopsy specimen, the sampling method and interobserver variations (22). The highest concordance between biopsy and Radical Prostatecomy analysis in Single Positive Core Patients occurs when the patient has a low-volume prostate and low PSA level.…”
Section: Discussionmentioning
confidence: 98%
“…Yet, if the cancer does metastasize, the disease becomes lethal, as there is currently no cure. At present, predictions of the course of the disease in an individual patient using current prognostic markers have substantial limitations [4][5][6][7]. Thus, while a broad spectrum of approaches, from "watchful waiting" and hormone deprivation therapy to surgical, radiation, and cryosurgical therapies, are available, it is not a simple task to assign an individual patient to the most appropriate treatment strategy.…”
Section: Prostate Cancer Diagnosis Prognosis and Treatmentmentioning
confidence: 99%
“…Clinical (digital rectal exam (DRE)), pathologic (histologic grade from biopsy, and number and percentage of positive biopsies) [8], and biochemical parameters in serum (PSA, PAP) [9][10][11][12] or in tissue (MIB-1, bcl-2, p53, CD34) [13][14][15][16][17] can aid in assessing the extent and aggressiveness of the disease. However, these are often inaccurate or inadequate, particularly when used alone in individual patients for both pre-and post-treatment assessments [4,5] [18].…”
Section: Prostate Cancer Diagnosis Prognosis and Treatmentmentioning
confidence: 99%
“…Half of those diagnosed have a Gleason score of 6 or lower (6), which has very low metastatic potential, and the proper clinical treatment for these men is unclear. Indeed, upon removal of the prostate and subsequent histologic analysis, the Gleason score is often revised, and an upgrade upon surgery is associated with adverse prognosis (7)(8)(9). Hence, there is an unmet need for improved diagnostics and risk assessment.…”
Section: Introductionmentioning
confidence: 99%